EFFECTIVENESS OF THE PEPAYA LEAF (Carica papaya Linn)ETHANOL EXTRACT AS LARVACIDE FOR AEDES AEGYPTI INSTAR III - Kurniawan, Betta; Rapina, Rama; Sukohar, Asep; Nareswari, Shinta (Majority, 2015)
Abstract Dengue Hemorrhagic Fever(DHF) is an infectious disease caused by thedengue virus is transmitted to humans by the bite of Aedes aegypty. Therefore the use of naturalin secticides, one of papaya(Carica papaya L.) which contains flavonoids, alkaloids and the enzyme papain which suspect the effect of larvicides. The study aims to determine the effectiveness of the ethanol extract of papaya (Carica papaya L.) as larvicides against Aedes aegypti larvae. This type of research is completely randomized experimental design. The total sample of 600 larvae were divided into 6 groups : 0% (negative control); 0.25%; 0.75%; 1% and Abate 1% (positive control). Each group contained 25 larvae with 4 repetitions. The data obtained were analyzed using the Kruskal-Wallis test, Mann Whitney and Post Hoc Test Simple Linear Regression. The results showed that the mean larve lmortality was 67%, 71%, 85%, 95% at a concentration of 0.25%, 0.50%, 0.75% and 1% concentration. Ethanol extract of leaves of papaya (Carica papaya L.) effective as larvicides against third instarlarvae of Aedes aegypti. LC50 value is 0.37% concentration and LT50 value is 1981 minutes. Keywords: Aedesaegypti, dengue hemoragic fever, Carica papaya L, larvicides Abstrak Demam Berdarah Dengue (DBD) adalah penyakit menular disebabkan oleh virus dengue yang ditularkan ke manusia dengan gigitan nyamuk Aedes Aegypty. Oleh karena itu digunakan insektisida alami, salah satunya daun pepaya (Carica papaya L.) yang mengandung senyawa flavonoid, alkaloid dan enzim papain yang diduga memilki efek larvasida. Penelitian bertujuan untuk mengetahui efektivitas ekstrak ethanol daun pepaya (Carica papaya L.) sebagai larvasida terhadap larva Aedes aegypti. Jenis penelitian yang digunakan adalah eksperimental dengan rancangan acak lengkap. Jumlah sampel sebanyak 600 larva dibagi menjadi 6 kelompok yaitu 0% (kontrol negatif); 0,25%; 0,75%; 1% dan abate 1% (kontrol positif). Setiap kelompok berisi 25 larva dengan 4 kali pengulangan. Data yang diperoleh dianalisis dengan menggunakan uji Kruskal- Wallis, Post Hoc Mann Whitney dan Uji Regresi Linear Sederhana. Dari hasil penelitian menunjukkan bahwa rerata kematian larva adalah 67%, 71%, 85%, 95% pada konsentrasi 0,25%, 0,50%, 0,75% dan konsentrasi 1%. Ekstrak ethanol daun pepaya (Carica papaya L.) efektif sebagai larvasida terhadap larva Aedes aegypti instar III. Nilai LC50adalah 0,37% konsentrasi dan nilai LT50 adalah 1981 menit. Kata kunci: Aedes aegypti, demam berdarah dengue, Carica papaya L., larvasida